(untitled) (Journal of Informatics and Mathematical Sciences, 2020)
In this paper we propose a new approach for the solution of second order fuzzy initial value problem without converting to a system of linear fuzzy differential equations using Runge Kutta Method of fourth order under H-differentiability especially increasing length of support. Numerical examples are provided to show the stability and convergence of the proposed method with error control.